A clinical, dermoscopic, histopathological and immunohistochemical study of melasma and facial pigmentary demarcation lines in the skin of color. Issue 6 (17th November 2020) - Khunger, Niti; Kandhari, Rajat; Singh, Avninder; Ramesh, V.
Abstract: Melasma and facial pigmentary demarcation lines (FPDL) are common causes of patterned facial pigmentation that may mimic each other. There is a paucity of studies investigating these two conditions. The objective of this study was to make a detailed comparative analysis of these disorders. A clinical, dermoscopic, histopathological and immunohistochemical analysis of lesional and perilesional skin was conducted in 20 patients each of melasma and FDPL. The most common morphological patterns were centrofacial in melasma and W‐shaped pattern in FPDL. Dermoscopy in melasma revealed similar patterns in lesional and perilesional skin, whereas FPDL did not. Histopathology of melasma revealed increased melanin in the suprabasal and basal layers (100%), melanophages in the upper dermis and solar elastosis (65%) in contrast to FPDL, wherein increased basilar melanin (75%) and dermal melanophages were the key findings. Expression of vascular endothelial growth factor and stem cell factor was slightly increased in lesional melasma skin, but not in FPDL. The study was limited by its small sample size and immunohistochemistry carried out in a few patients. Melasma and FPDL, although similar in presentation, are distinct entities. Dermoscopy, histology and immunohistochemistry reveal subtle differences.